Analysis of dirac systems and computational algebra - Colombo, Fabrizio; Sabadini, Irene; Sommen, Franciscus; Struppa, Daniele C. (Boston: Birkhauser, 2004)
The subject of Clifford algebras has become an increasingly rich area of research with a significant number of important applications not only to mathematical physics but to numerical analysis, harmonic analysis, and computer science. The main treatment is devoted to the analysis of systems of linear partial differential equations (PDEs) with constant coefficients, focusing attention on null solutions of Dirac systems.Knowledge from different fields of mathematics such as commutative algebra, Grobner bases, sheaf theory, cohomology, topological vector spaces, and generalized functions (distributions and hyperfunctions) is required of the reader. However, all the necessary classical material is initially presented.The book may be used by graduate students and researchers interested in (hyper)complex analysis, Clifford analysis, systems of PDEs with constant coefficients, and mathematical physics.
Bibliography 313-326p.; Index 327-332p.
Keywords: Computational algebra; Differential equations; Dirac equation; Mathematical physics; Mathematics